WARM COMPRESS EFFECTIVENESS IN REDUCING DYSMENORRHOEA PAIN INTENSITY ON STIKES RS. BAPTIS KEDIRI STUDENTS - Anugraheni, Vonny Merdianita Dwi; Wahyuningsih, Aries (Jurnal Penelitian STIKES Kediri, 2013)
Abdominal muscle contraction that occurs continuously as blood discharge during menstruation will cause pain (dysmenorrhoea). Giving warm compress will be dilates blood vessels and increase local blood flow which resulting relaxation and can reduce pain. The purpose of research was to analyze warm compress as an effort to decrease dysmenorrhoeaâ€™s pain intensity. The design of this research was pre-experimental one group pre-post test design. The population was 4th grade students of STIKES RS. Baptis Kediri who experienced Dysmenorrhoea that met inclusion criteria. The samples were 30 respondents. The data were analyzed using Wilcoxon Signed Ranks Test with significant level Î± â‰¤ 0.05. The results showed 16 respondents (53.3%) experienced severe pain and 14 respondents (46,7%) experienced moderate pain before given warm compress. After given warm compress, 19 respondents (63.3%) experienced mild pain and 11 responden (36,7%) experienced moderate pain. The conclusion is warm compresses can reduce the intensity of severe pain to mild pain in dysmenorrhoea women.